Competency-Based Training Model in Job Training Centers: Answering Today's Employment Challenges - Widayati, Tri; Pudjiarti, Emiliana Sri (Universitas 17 Agustus 1945, 2024)
This study aims to develop a hypothetical model of Balai Latihan Kerja (BLK) / Job Training Center through the POAC (Planning, Organizing, Actuating, Controlling) approach as a fundamental framework in reforming the vocational training system. Using qualitative methods with data triangulation from expert interviews, empirical studies, and international reports, the study identified four key themes that determine the effectiveness of the model: digital transformation, strengthening triple helix partnerships, sustainable competency development, and industry-based standardization and certification. Digital transformation through virtual reality-based simulations and digital learning platforms has increased training effectiveness by up to 48%. Triple helix partnerships increase graduate absorption rates by up to 78%. Sustainable competency development is essential, considering that 65% of jobs in 2030 will require skills that do not yet exist today. Industry-based standardization positively correlates with labour productivity, increasing it by 24%. The hypothetical Balai Latihan Kerja (BLK) model that integrates these four themes is expected to be a reference in preparing an adaptive, competitive workforce that is ready to face global challenges in the era of technological disruption.